Emerging protein kinase inhibitors for treating pancreatic cancer. (2nd January 2017) - Furuse, Junji; Nagashima, Fumio
ABSTRACT: Introduction : Pancreatic cancer, the incidence and mortality of which are increasing around the world, has the most dismal prognosis among the commonly encountered cancers. Systemic chemotherapy plays an important role in the treatment of patients with pancreatic cancer, and development of more effective chemotherapies is being sought. Areas covered : This review article provides a summary about protein kinase inhibitors that have been investigated for the treatment of pancreatic cancer, not only existing agents targeting RAS, EGFR, VEGFR, MEK, etc., but also various compounds targeting, including the MAPK, PI3 K/Akt/mTOR, and JAK/STAT signaling pathways, trials of which are currently ongoing. To date, none has shown sufficient efficacy as to merit becoming established as a standard treatment agent for pancreatic cancer. Expert opinion : As the toxicities of protein kinase inhibitors usually differ from those of cytotoxic agents, it could be of value to use these agents in combination with gemcitabine plus nab-paclitaxel. It may be reasonable to identify a suitable disease and/or predictive markers for new compounds in proof of concept trials. It is an urgent need to conduct phase III trials, on the basis of the results obtained, in subpopulations with biomarkers to predict the efficacy of these drugs.